Effect of upstream crest length on flow characteristics and discharge capacity of triangular labyrinth side weirs - Kaya, Nihat (Academic Journals, 2010)
A series of laboratory experiments were performed within this study in order to investigate the hydraulic characteristics and the discharge capacity of sharp-crested triangular labyrinth side weirs with various upstream crest lengths. To conduct the experiment series, twenty seven different labyrinth side weir models having triangular plan view that are manufactured from steel were tested in the laboratory flume. A labyrinth weir is an overflow weir that is folded in plan view to provide a longer total effective length for a given overall weir width. To estimate the outflow over a side weir, the discharge coefficient in the side weir equation needs to be determined. A comprehensive laboratory study including 679 tests was conducted to determine the discharge coefficient of the side weirs. It was found that the discharge coefficient of triangular labyrinth side weirs was higher than that of classical side weirs. In addition, reliable equations to calculate the discharge coefficient of side weirs are presented.
Keywords: Side weir; discharge coefficient; labyrinth weir; hydraulic structure; open channel flow